2020
DOI: 10.1037/cou0000400
|View full text |Cite
|
Sign up to set email alerts
|

Can we agree we just had a rupture? Patient-therapist congruence on ruptures and its effects on outcome in brief relational therapy versus cognitive-behavioral therapy.

Abstract: To draw clinically meaningful evidence-supported implications about the alliance-outcome association, recent studies have investigated patient-therapist congruence on ruptures in alliance. The present study investigated patient-therapist congruence on ruptures and its consequences on subsequent session outcome in 2 types of treatments that differ in the training therapists receive to identify ruptures: brief relational therapy (BRT), in which therapists receive alliance-focused training, and cognitive-behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 48 publications
(99 reference statements)
2
18
0
Order By: Relevance
“…This may be because of these therapists’ higher self-efficacy in general than the other therapists. On the other hand, as Zilcha-Mano, Eubanks, Bloch-Elkouby, and Muran (2020) found out, therapists who were more attuned to their patients may demonstrate greater vigilance in identifying alliance ruptures; therefore, it’s possible that the therapist’s general level of attunement with the client may help the therapist better see from the client’s perspective, leading to less unique individual perceptions on the therapist’s part. Further along this line, therapists who are more skilled in working within the therapeutic relationship may be more able to communicate and discuss with the client about their alliance and the therapy process (Samstag & Muran, 2019) and thus develop a greater shared collective perception of the therapy process and outcome and have less individual unique perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because of these therapists’ higher self-efficacy in general than the other therapists. On the other hand, as Zilcha-Mano, Eubanks, Bloch-Elkouby, and Muran (2020) found out, therapists who were more attuned to their patients may demonstrate greater vigilance in identifying alliance ruptures; therefore, it’s possible that the therapist’s general level of attunement with the client may help the therapist better see from the client’s perspective, leading to less unique individual perceptions on the therapist’s part. Further along this line, therapists who are more skilled in working within the therapeutic relationship may be more able to communicate and discuss with the client about their alliance and the therapy process (Samstag & Muran, 2019) and thus develop a greater shared collective perception of the therapy process and outcome and have less individual unique perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…We also included the main effects of the targeted IIP-32 dimensions in the regression. Considering that in the present sample, we had repeated measures of both the predictors and the outcome variables, we followed the procedures presented by Zilcha-Mano, Eubanks, Bloch-Elkouby, and Muran (2020) to adjust for time effects by including the session number (centered at the first session) as a predictor. Before calculating the quadratic and interactive terms, the predictors were grand-mean centered (Marmarosh & Kivlighan, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…A recent meta-analysis based on 295 studies suggested that a stronger alliance is a significant predictor of better treatment outcome across treatment orientations and patient populations [ 5 , 6 ] This finding may be an indication of a robust TL effect, where, on average, patients who form a stronger alliance also exhibit greater treatment response. However, such TL finding does not translate directly into clinical practice so that therapists will be able to improve the alliance with individual patients to facilitate therapeutic change [ 7 , 8 , 9 , 10 , 11 ]. Contemporary theoretical conceptualizations suggest that the effect of the alliance varies with different subpopulations of patients and across different treatments.…”
Section: The Utility Of the Sl–tl Distinction In Psychotherapy Resear...mentioning
confidence: 99%